1962
DOI: 10.1111/j.1365-2621.1962.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

The Flavor of Cucumbers

Abstract: Nona-2,6-dienal, non-2-enal, hex-2-enal, and three saturated aliphatic aldehydes were isolated from cucumbers.Quantitative and qualitative aspects of the flavor of nona-2,6-dienal and non-2-enal were examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

1969
1969
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(65 citation statements)
references
References 8 publications
6
59
0
Order By: Relevance
“…Different letters represent significant differences (P<0.05) between the mean numbers of flies caught (ANOVA, followed by Tukey's HSD) and Wasternack 2002), and have been found previously in both fresh and fermented cucumbers (Kemp et al 1974;Zhou and McFeeters 1998). The predominant volatile isolated from fresh blended cucumber is E2Z6-9:al, which is also the most important compound in producing the characteristic cucumber smell perceived by humans (Forss et al 1962;Schieberle et al 1990). Interestingly, several LOX pathway derivatives, or close analogs, have been implicated previously in melon fly attraction.…”
Section: Discussionmentioning
confidence: 95%
“…Different letters represent significant differences (P<0.05) between the mean numbers of flies caught (ANOVA, followed by Tukey's HSD) and Wasternack 2002), and have been found previously in both fresh and fermented cucumbers (Kemp et al 1974;Zhou and McFeeters 1998). The predominant volatile isolated from fresh blended cucumber is E2Z6-9:al, which is also the most important compound in producing the characteristic cucumber smell perceived by humans (Forss et al 1962;Schieberle et al 1990). Interestingly, several LOX pathway derivatives, or close analogs, have been implicated previously in melon fly attraction.…”
Section: Discussionmentioning
confidence: 95%
“…In general, the relative percentage of aldehyde compounds decreased as fruit growth progressed, and there were more esters and acetates recovered from mature fruits. In the very beginning, (E,Z)-2,6-nonadienal and (E)-2-nonenal commanded an overwhelming majority (totally higher than 80%), and they are reported as the first and second major components contributed to the pleasant odor in cucumber (Cucumis sativus L.), respectively (Forss et al, 1962;Schieberle et al, 1990). In fact, not only did 17 DAP fruits smell like cucumber, but also tasted like cucumber.…”
Section: Research Reportmentioning
confidence: 96%
“…This odorant is well recognized as the character-impact compound of cucumber. [39] Our work revealed that it is also the most impactful compound of honeydew melon aroma. Odorants S and V showed the second highest FD factor; they respectively imparted fresh and sweet-fl oral characters to honeydew melon aroma.…”
Section: Aroma Extract Dilution Analysis Of Honeydew Melonmentioning
confidence: 96%